ANALISIS KONTRIBUSI SEKTOR KOMODITAS KARET TERHADAP PERTUMBUHAN EKONOMI KABUPATEN BANYUASIN TAHUN 2016-2021 - Zulhan, Muhamad Zulhan Fikri; Nurul Badriyah (Journal of Development Economic and Social Studies, 2024)
This research aims to analyze the contribution of the rubber commodity sector to the economic growth of Banyuasin Regency from 2016 to 2021, along with the specialization level of this sector. The study employs a quantitative research method designed to illustrate correlations with appropriate reliability and priority levels. Analytical methods utilized include Location Quotient (LQ) and Shift-share (SS). Secondary data for the research are sourced from the Central Statistics Agency (BPS) of Banyuasin Regency and South Sumatra Province. The findings reveal that, among the 21 sub-districts in Banyuasin Regency, a majority exhibit rubber plantation as their primary sub-sector, evident from the average LQ calculations. The LQ and Shift-share results, where LQ>1 and PPW>0, indicate that 10 sub-districts serve as the base sectors for the rubber commodity, positively impacting the economy of Banyuasin Regency. Moreover, six sub-districts with LQ>1 and PPW<0 show that high production values and rubber plantation mobility contribute negatively due to less effective supporting mobility, thereby preventing high yields from translating into positive economic values for Banyuasin Regency. Additionally, five sub-districts with LQ<1 signify that rubber plantations have not yet emerged as leading sectors in these areas.